Implementation of Wattpad in Understanding Popular Literature as an Effort for Improving Reading Comprehension - Dinar Faiza; Ade Christanty Yudha Bestari (Jurnal Sinestesia, 2023)
This study aimed to examine the implementation of using Wattpad in understanding popular literature as an effort to train reading comprehension for English Education students at UNU Purwokerto. Researchers applied Wattpad as an alternative medium for learning to read popular literature. The research method used descriptive qualitative. Data collection used purposive sampling by taking a sample of 21 students. Data collection techniques used tests, interviews, observation, and documentation. Through this research, several findings were found. First, by using Wattpad, it increases reading comprehension of popular literary works. It is seen from 76% of students having a "good and very good" category in the score range of 76-93. This improvement is most visible in understanding the intrinsic elements of theme, characterizations, plot, setting, point of view and moral values. Second, the perception of students stated that Wattpad is effective learning media in reading because it is a free application that is easily accessible anytime and anywhere. Third, the use of Wattpad increases an interest in reading because there is variety of interesting stories that stimulates curiosity, need, and pleasure to continue reading activities.